Students' Cognitive Style and Their Ratings of Their Teacher's Effectiveness - Dona M. Kagan; Yvonne Tixier y Vigil (Educational Considerations, 1987)
An instructor's behavior may be perceived as more important or more effective by students whose cognitive style is compatible with the instructor's teaching style.